Development, characterization, and reversal of acquired resistance to the MEK1 inhibitor selumetinib (AZD6244) in an in vivo model of childhood astrocytoma - Bid, Hemant Kumar; Kibler, Aaron; Phelps, Doris A.; Manap, Sagymbek; Xiao, Linlin; Lin, Jiayuh; Capper, David; Oswald, Duane; Geier, Brian; DeWire, Mariko; Smith, Paul D.; Kurmasheva, Raushan T.; et al. (Clinical cancer research, 2013)
Purpose: The BT-40 low-grade childhood astrocytoma xenograft model expresses mutated BRAFV600E and is highly sensitive to the MEK inhibitor selumetinib (AZD6244). In this study, we developed and characterized selumetinib resistance and explored approaches to circumventing the mechanisms of acquired resistance. - Experimental Design: BT-40 xenografts were selected in vivo for selumetinib resistance. Resistant tumors were obtained and characterized, as were tumors that reverted to sensitivity. Characterization included expression profiling, assessment of MEK signature and compensatory pathways, MEK inhibition, BRAF expression, and cytokine levels. Combination treatment of BT-40/AZD-resistant tumors with the MEK inhibitor and a STAT3 inhibitor (LLL12) was assessed. - Results: Resistance was unstable, tumors reverting to selumetinib sensitivity when passaged in untreated mice, and MEK was equally inhibited in sensitive and resistant tumors by selumetinib. Drug resistance was associated with an enhanced MEK signature and increased interleukin (IL)-6 and IL-8 expression. Selumetinib treatment induced phosphorylation of STAT3 (Y705) only in resistant xenografts, and similar results were observed in BRAFV600E astrocytic cell lines intrinsically resistant to selumetinib. Treatment of BT-40-resistant tumors with selumetinib or LLL12 had no significant effect, whereas combined treatment induced complete regressions of BT-40/AZD-resistant xenografts. - Conclusions: Resistance to selumetinib selected in vivo in BT-40 tumor xenografts was unstable. In resistant tumors, selumetinib activated STAT3, and combined treatment with selumetinib and LLL12 induced complete responses in resistant BT-40 tumors. These results suggest dual targeting BRAF (V600E) signaling and STAT3 signaling may be effective in selumetinib-resistant tumors or may retard or prevent onset of resistance. Clin Cancer Res; 19(24); 6716-29. ©2013 AACR.
Gesehen am 25.11.2020